POLA KEMITRAAN USAHA BUDIDAYA TAMBAK UDANG VANAME (Litopenaeus vannamei) DI PT. BANGKA BELITUNG MARITIM SEJAHTERA DESA PASIR PUTIH KECAMATAN TUKAK SADAI KABUPATEN BANGKA SELATAN - Cafrina, Nadia; Bidayani, Endang; Andri Kurniawan, Andri (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Bangka Belitung Islands is a province that has great potential in the development of the fisheries sector, especially the aquaculture of vaname shrimp (Litopenaeus vannamei). One of the companies engaged in fishery at the stage of growing vaname shrimp is PT. Bangka Belitung Maritime Prosperity. In this regard, efforts must be made to develop the cultivation business. One of them is through partnership cooperation. The purpose of this thesis research is to describe the form of business partnership pattern between PT. Bangka Belitung Maritim Sejahtera with partners who join, examine the strengths and weaknesses in the implementation of the partnership and analyze the efforts made by PT. Bangka Belitung Maritim Prosperous in maintaining partnership relations. This research is a qualitative research with a descriptive approach and data collection techniques using documentation, observation and interviews. Sampling through purposive sampling technique that begins with the general manager of PT. Bangka Belitung Maritim Sejahtera then turned to four other partners. The results showed that there are three types of partnership patterns that exist in PT. Bangka Belitung Maritim Sejahtera, namely the sub-contract partnership pattern, the general trade partnership pattern and the plasma core partnership pattern. This partnership pattern resulted from a partnership between PT. Bangka Belitung Maritim Sejahtera with five partnering companies/groups. The advantages of implementing a vaname shrimp enlargement business partnership at PT. Bangka Belitung Maritim Sejahtera is the provision of consultation and guidance on cultivation, providing input for production facilities, obtaining technical knowledge, guaranteeing market certainty, strengthening the company's brand image and opening opportunities to support the prospect of sustainable agribusiness partnerships in the fisheries sector. While the weaknesses in the implementation of this partnership are the buying and selling price determined by the partner company, the absence of a written contract agreement between the core company and the partner company, the delivery process of shrimp fry that is not good, and late payments made by partner companies. Efforts made by PT. Bangka Belitung Maritim Sejahtera in maintaining partnership relationships are conducting interactive communication with partner companies, building a good cooperation system, providing handling of problems that occur, holding the principle of mutual trust, supporting partner companies in business development, and updating information through group chat applications and the company website. .